Convergence in Corporations Law - Towards a Facilitative Model - Goddard, David (Victoria University of Wellington Law Review, 1996)
The following is the Report of the General Reporter on the Law of Corporations presented to the Annual Colloquium of the International Association of Legal Science (the 1995 IALS Colloquium) which was held in Buenos Aires in September 1995. The theme of the conference was "Towards a modern ius commune: converging trends in a changing world". This article argues that there has been a significant degree of convergence internationally in the general approach of states to corporations law. The article begins by setting out the purpose and justifications of corporations in a modern economy: the division of ownership interest into shares, the limited liability of the shareholders, and the nature of risk-taking and risk-bearing. The article then provides the evidence of both convergence and divergence in corporations law, ultimately arguing for there being a convergence. The author also provides some insight into the likely directions for convergence. The author concludes that the overall movement towards a facilitative model of corporations law is a self-reinforcing process which can be expected to become even more widespread and rapid in the future.